The nicotinic acetylcholine receptor: from molecular model to single-channel conductance. - Adcock, C; Smith, G; Sansom, MS (2000)
The nicotinic acetylcholine receptor (nAChR) is the archetypal ligand-gated ion channel. A model of the alpha7 homopentameric nAChR is described in which the pore-lining M2 helix bundle is treated atomistically and the remainder of the molecule is treated as a "low resolution" cylinder. The surface charge on the cylinder is derived from the distribution of charged amino acids in the amino acid sequence (excluding the M2 segments). This model is explored in terms of its predicted single-channel properties. Based on electrostatic potential profiles derived from the model, the one-dimensional Poisson-Nernst-Planck equation is used to calculate single-channel current/voltage curves. The predicted single-channel conductance is three times higher (ca. 150 pS) than that measured experimentally, and the predicted ion selectivity agrees with the observed cation selectivity of nAChR. Molecular dynamics (MD) simulations are used to estimate the self-diffusion coefficients (D) of water molecules within the channel. In the narrowest region of the pore, D is reduced ca. threefold relative to that of bulk water. Assuming that the diffusion of ions scales with that of water, this yields a revised prediction of the single-channel conductance (ca. 50 pS) in good agreement with the experimental value. We conclude that combining atomistic (MD) and continuum electrostatics calculations is a promising approach to bridging the gap between structure and physiology of ion channels.